Exploration of the springs of the northern part of the Chuvash Republic, Russia - Nikonorova Inna; Ilyin Vladimir; Gumenuk Anna; Ilyina Anastasia; Nikitin Andrey (BIO Web of Conferences)
The paper presents the reasons for the appearance of a dense network of well-maintained springs on the territory of the Chuvash Republic. Materials on the study of the quality of spring water in the northern part of the Chuvash Republic are presented. Parameters such as the physical properties of water, chemical composition, environmental condition of the surrounding area, safety of landscaping facilities, type of use of the spring, frequency of use are described. A total of 20 springs from 10 municipalities were examined. The chemical analysis of spring water included a description of 10 parameters, no excess of permissible parameters in terms of pollutants was detected. The main types of use of springs have been established: economic and drinking, religious, and environmental. The frequency of use of springs is analyzed: from abandoned to regularly used. The recreational potential of springs has been calculated. The main factors influencing the value of the recreational potential of the springs of the Chuvash Republic are described.